Evaluating Environment in International Development - Uitto, Juha I. (2021)
This book provides novel and in-depth perspectives on evaluating environment and sustainability issues in developing countries. Evaluating Environment in International Development focuses on the approaches and experiences of leading international organizations, not-for-profits, and multilateral and bilateral aid agencies to illustrate how systematic evaluation is an essential tool for providing evidence for decision-makers. Moving beyond projects and programmes, it explores normative work on the environment as well as environmental consequences of economic and social development efforts. This new edition reflects on the 2030 Agenda for Sustainable Development and Sustainable Development Goals and considers how they have influenced efforts in a wide range of countries and what the implications are for evaluation. It also explores ways in which Big Data and geospatial approaches might be utilized. Significantly updated throughout to reflect recent developments in climate change research, and on the implications of the 2020 pandemic, this volume will be of great interest to students and scholars of environment studies, development studies, international relations, sustainable development and evaluation, as well as practitioners in international organizations and development and environmental NGOs.